Intravenous Insulin Treatment in Acute Stroke: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. Issue 4 (June 2014) - Ntaios, G.; Papavasileiou, V.; Bargiota, A.; Makaritsis, K.; Michel, P.
Introduction: Poststroke hyperglycemia has been associated with unfavorable outcome. Several trials investigated the use of intravenous insulin to control hyperglycemia in acute stroke. This meta-analysis summarizes all available evidence from randomized controlled trials in order to assess its efficacy and safety. Methods: We searched PubMed until 15/02/2013 for randomized clinical trials using the following search items: 'intravenous insulin' or 'hyperglycemia', and 'stroke'. Eligible studies had to be randomized controlled trials of intravenous insulin in hyperglycemic patients with acute stroke. Analysis was performed on intention-to-treat basis using the Peto fixed-effects method. The efficacy outcomes were mortality and favorable functional outcome. The safety outcomes were mortality, any hypoglycemia (symptomatic or asymptomatic), and symptomatic hypoglycemia. Results: Among 462 potentially eligible articles, nine studies with 1491 patients were included in the meta-analysis. There was no statistically significant difference in mortality between patients who were treated with intravenous insulin and controls (odds ratio: 1·16, 95% confidence interval: 0·89–1·49). Similarly, the rate of favorable functional outcome was not statistically different (odds ratio: 1·01, 95% confidence interval: 0·81–1·26). The rates of any hypoglycemia (odds ratio: 8·19, 95% confidence interval: 5·60–11·98) and of symptomatic hypoglycemia (odds ratio: 6·15, 95% confidence interval: 1·88–20·15) were higher in patients treated with intravenous insulin. There was no heterogeneity across the included trials in any of the outcomes studied. Conclusions: This meta-analysis of randomized controlled trials does not support the use of intravenous insulin in hyperglycemic stroke patients to improve mortality or functional outcome. The risk of hypoglycemia is increased, however.